2019
DOI: 10.31728/jnn.2019.00042
|View full text |Cite
|
Sign up to set email alerts
|

Patent Foramen Ovale: Risk Factors and Diagnostic Comparison of Transcranial Doppler versus Echocardiography for Secondary Stroke Prevention

Abstract: Various factors correlated to PFO that tend to increase its causal relationship with cryptogenic ischemic stroke include: young age, valsalva maneuver (VM), recent prolonged immobility, concomitant DVT in legs or pelvis, presence of atrial septal aneurysm (ASA), history of migraine with aura, and neuroimaging demonstrating solitary cortical or bilateral embolic pattern. 3 Few of these factors have been discussed in the following section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…46 Most studies have found that TCD is at least not inferior to TEE for detecting right-to-left shunting. 51,52 In one study, TCD was marginally superior to TEE (by almost 5%). 53…”
Section: Accuracy Of Testing For Pfo With Agitated Saline Bubblesmentioning
confidence: 99%
“…46 Most studies have found that TCD is at least not inferior to TEE for detecting right-to-left shunting. 51,52 In one study, TCD was marginally superior to TEE (by almost 5%). 53…”
Section: Accuracy Of Testing For Pfo With Agitated Saline Bubblesmentioning
confidence: 99%